Editorial practices between evolution, manipulation and adaptation : Case of Gabon. Historical and semiotic approach - (:unkn) unknown (My University, 2018)
The book and publishing sector in French-speaking Black Africa is very much inspired by the Western editorial model, particularly that of France. The book in the West has gradually been put in place to have the form and notoriety that is his today, it is the same for publishing and the profession of publisher. In black Francophone Africa, this sector goes through the same path which is the progressive evolution, however it no longer concerns the creation of the elements that make up the book and the edition, but rather the practice itself which is struggling to hatch. Truly despite the contributions of various international institutions and local arrangements. Indeed, in this study, we found problems common to all the countries of French-speaking Black Africa, as well as the difficulties specific to each country. Gabon is the country on which we mainly rely. The various researches allowed us to take up the major difficulties that undermine the book and publishing sector in French-speaking Black Africa, but especially to make an inventory of the general situation of this sector.First and foremost, the book and publishing sector comes under the domain of history and sociology. Through the semiotics of Yuri Lotman's cultures, we have found elements of the book and the edition that integrate culture as well. The sector under study can thus lend itself to a more comprehensive study.
Keywords: African Research